2019
DOI: 10.1021/acs.langmuir.9b00636
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Behavior and in Situ Confocal Imaging of Bijels Made by Mixing

Abstract: Bijels (bicontinuous interfacially jammed emulsion gels) have the potential to be useful in many different applications due to their internal connectivity and the possibility of efficient mass transport through the channels. Recently new methods of making the bijel have been proposed which simplify the fabrication process making commercial application more realistic. Here we study the flow properties of bijels prepared by mixing alone using oscillatory rheology combined with confocal microscopy and also squeez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 43 publications
4
16
0
Order By: Relevance
“…Oscillatory amplitude sweep experiments were conducted by performing three oscillation cycles at a fixed frequency of o = 6.3 Â 10 À1 rad s À1 and strains spanning from g = 1.0 Â 10 À2 % to 1.0 Â 10 3 %. Since amplitude sweeps extend to large strains that plastically deform the microstructure of bijels, 31 each of these tests was conducted on a separate bijel.…”
Section: Bijel Rheologymentioning
confidence: 99%
See 2 more Smart Citations
“…Oscillatory amplitude sweep experiments were conducted by performing three oscillation cycles at a fixed frequency of o = 6.3 Â 10 À1 rad s À1 and strains spanning from g = 1.0 Â 10 À2 % to 1.0 Â 10 3 %. Since amplitude sweeps extend to large strains that plastically deform the microstructure of bijels, 31 each of these tests was conducted on a separate bijel.…”
Section: Bijel Rheologymentioning
confidence: 99%
“…Macmillan et al reported irreversible breakdown of the bicontinuous structure of bijels formed by direct mixing at large strains. 31 It is likely that bijels formed through spinodal decomposition experience the same microstructural changes at or near the G 0 -G 00 crossover. For capillary suspensions, the linear viscoelastic regime extends only to g E 0.05%, and the transition to non-linearity is marked by a sharp decline in both G 0 and G 00 with a power-law exponent of n E À1.…”
Section: Beyond Linear Viscoelasticity: Comparison To An Attractive S...mentioning
confidence: 99%
See 1 more Smart Citation
“…The work of Cai et al, and follow-up work by li et al and macmillan et al, which combined systematic investigation of the formation of bijels by stirring in tandem with careful formulation optimisation, pro-vides some insight here (Figure 9.17). [71][72][73] This work studied a variant of the nanoparticle surfactant system developed by ravera et al, 74,75 in which silica nps and cetyltrimethylammonium bromide (CTab, a cationic surfac-tant) are dispersed in a polar phase. The CTab modifies the surface chem-istry of the nanoparticles in situ, forming CTab-SinpS that readily adsorb to the liquid-fluid interface.…”
Section: Bijels By Direct Mixingmentioning
confidence: 99%
“…By tuning the mass ratio ( M ) of oppositely charged nanoparticles (OCNPs), a desired wetting condition, i.e., θ < 90° or ≈ 90°, is achieved. Bijels have been identified as the new class of soft materials in which the self-assembly of colloidal particles creates a novel bicontinuous structure. , Unlike emulsion droplets, since the θ established by the particles at the interface is nearly 90°, these bijels stabilized by OCNPs exhibit strong attachment energy, making them suitable for applications that involve multicomponent or multiphase flows. The resulting bijels could be potentially used as the cross-flow microreactors , wherein two-immiscible reactants can be brought into intimate contact through interstitial sites, scaffolds for tissue engineering, porous materials, and electrodes for batteries and fuel cells .…”
Section: Introductionmentioning
confidence: 99%